2013
DOI: 10.1002/cncr.28294
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 and pharmacodynamic trial of everolimus in combination with cetuximab in patients with advanced cancer

Abstract: BACKGROUND:Preclinical and clinical studies suggest mTOR (mammalian target of rapamycin) inhibitors may have metabolic and antiangiogenic effects, and synergize with epidermal growth factor pathway inhibitors. Therefore, a phase 1/pharmacodynamic trial of everolimus with cetuximab was performed. METHODS: A total of 29 patients were randomized to a run-in of oral everolimus (30, 50, or 70 mg) or cetuximab (400 mg/m 2 loading, 250 mg/m 2 maintenance) weekly, followed by the combination in this dose-escalation st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…(), Ciunci et al. () reported the incidence rates limited to grades 2, 3, and 4 treatment‐related toxicities; for this reason, data about cases of stomatitis and stomatitis grade 1 are lower than real.…”
Section: Resultsmentioning
confidence: 99%
“…(), Ciunci et al. () reported the incidence rates limited to grades 2, 3, and 4 treatment‐related toxicities; for this reason, data about cases of stomatitis and stomatitis grade 1 are lower than real.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the results of a phase 1 trial combining everolimus with cetuximab were reported . This trial dose‐escalated everolimus to 30, 50, or 70 mg weekly with a standard fixed dose of cetuximab.…”
Section: Discussionmentioning
confidence: 99%
“…Model convergence was achieved (to >3 decimal places) with the conditional Laplace method, which allowed for η‐ω interactions (preference = COND LAP‐LACE INTER SLOW (computer commands to implement the conditions mentioned in the beginning of sentence)). The model diagnostics for the goodness of fit included the NONMEM objective function (OFV; −2 × log‐likelihood) and a visual inspection of graphics, such as the correlation/symmetry of observations versus predictions (population and post hoc) and conditional weighted residuals versus time and predictions . Statistical support for using a 2‐compartment model versus a 1‐compartment model (2 extra parameters) was obtained through comparisons of changes in OFV (ΔOFV); ΔOFV > 3.84 or 5.99 in nested models represented a statistical improvement for 1 or 2 additional estimated parameters, respectively ( P < .05, χ 2 ) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations